How hand-made affects consumers’ perceived nutritional quality of organic food - Liu, Qin; Cao, Jun; Li, Siyu; Wei, Yunyun; Ma, Conghong (Frontiers in Nutrition, 2024)
This study analyzed the impact of handmade in depth on consumers’ perceived nutritional quality of organic food through three experiments. Experiment 1 found that handmade significantly enhanced consumers’ positive perceptions of nutritional quality of organic food. Experiment 2 revealed the mediating role of handicraft cultural identity between handmade and perceived nutritional quality. Experiment 3 further explored the moderating role of perceived authenticity on the impact of handmade. We found that these factors above significantly enhanced the positive effect of handmade on perceived nutritional quality. The findings suggest that handmade directly affected consumers’ perceived nutritional quality of organic food, which could be further strengthened through the mediating effect of handcraft cultural identity and the moderating effect of perceived authenticity. These findings provide important guidance for organic food manufacturers and marketers on marketing strategy-making that can help better meet consumer demand for high-quality organic food.